Value Added Tax Reporting Procedures Using the Digital System at PT Alam Mulya - Islakhatul Fauziyah; Sri Trisnaningsih (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to determine the implementation of Value Added Tax reporting procedures using the Core Tax Administration System system at PT Alam Mulya. The method used is descriptive qualitative. This research was conducted through direct observation during internship activities at the Finance & Accounting Division of PT Alam Mulya. The results showed that the Core Tax Administration System provides convenience in the creation and reporting of digital tax invoices, can improve reporting accuracy, and minimize tax administrative errors. In addition, the Coretax system helps supervision to be tighter and easier to access. There are also some obstacles that still need to be evaluated more deeply. But overall, the implementation of the Core Tax Administration System at PT Alam Mulya has a positive impact that helps the company's efficiency and compliance strategies in the context of tax administration.